The application of modular multifunctional left heart bypass circuit system integrated with ultrafiltration in thoracoabdominal aortic aneurysm repair - Huang, Lingjin; Chen, Xuliang; Hu, Qinghua; Luo, Fanyan; Hu, Jiajia; Duan, Lian; Wang, E.; Ye, Zhi; Zhang, Chengliang (Frontiers in Cardiovascular Medicine, 2022)
Open thoracoabdominal aortic aneurysm (TAAA) repair is a complex and challenging operation with a high incidence of serious complications, and high perioperative mortality and morbidity. Left heart bypass (LHB) is a circulatory support system used to perfuse the distal aorta during TAAA operation, and the advantages of LHB include guaranteeing distal perfusion, reducing the use of heparin, and diminishing the risk of bleeding and postoperative neurological deficits. In China, the circuit for TAAA repair is deficient, and far from the perfusion requirements. We designed a modular multifunctional LHB circuit for TAAA repair. The modular circuit consisted of cannulation pipelines, functional consumables connection pipelines, and accessory pipelines. The accessory pipelines make up lines for selective visceral perfusion and kidney perfusion, suckers and rapid infusion. The circuit can be assembled according to surgical requirements. The ultrafilter and heat exchanger integrated into the circuit to fulfil basic demands of LHB. The LHB circuit also has pipelines for selective visceral perfusion to the celiac artery and superior mesenteric artery and renal perfusion pipelines. Meanwhile, the reserved pipelines facilitate the quick switch from LHB to conventional cardiopulmonary bypass (CPB). The reserved pipelines reduce the time of reassembling the CPB circuit. Moreover, the rapid infusion was integrated into the LHB circuit, which can rapid infusion when massive hemorrhage during the open procedures such as exposure and reconstruction of the aorta. The ultrafiltration can diminish the consequent hemodilution of hemorrhage and rapid infusion. A hemoperfusion cartridge also can be added to reduce the systemic inflammatory during operation. The circuit can meet the needs of LHB and quickly switch to conventional CPB. No oxygenator was required during LHB, which reduce the use of heparin and reduce the risk of bleeding. The heat exchanger contributes to temperature regulation; ultrafiltration, arterial filter, and rapid-infusion facilitated the blood volume management and are useful to maintain hemodynamic stability. This circuit made the assembly of the LHB circuit more easily, and more efficient, which may contribute to the TAAA repair operation performed in lower volume centers easily.